Complete mitochondrial genome of javeline goby (Synechogobius hasta). (1st November 2016) - Wang, Xiaodong; Chen, Dunxue; Zhou, Xianjun; Zhao, Falan; Yao, Junjie; An, Miao
Abstract: In this study, we cloned and sequenced the complete mitochondrial DNA (mtDNA) of Synechogobius hasta to characterize and compare their mitochondrial genomes. The total length of the mitochondrial genome is 16, 655 bp with an accession number KM891736. The organization of the mitochondrial genomes was similar to those reported from other fish mitochondrial genomes containing 37 genes (13 protein-coding genes, 2 ribosomal RNA and 22 transfer RNAs) and a major non-coding control region. Except for ND6 and 8 tRNAs, all other genes are encoded on the heavy strand. The base composition of the 13 mitochondrial protein-coding genes in the third position was relatively low (9.7%). The complete mitogenome may provide important date set for the study of genetic mechanism of S. hasta.